2009
DOI: 10.1038/ismej.2009.84
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of aerobic and anaerobic ammonia-oxidizing bacteria in marine sponges

Abstract: Aerobic ammonia-oxidizing bacteria (AAOB) are known to have an important function in the marine nitrogen cycle. Anaerobic ammonium oxidation (anammox) carried out by some members of Planctomycetales is also an important process in marine ecosystems. Ammonia-monooxygenase gene (amoA) fragments were amplified to investigate the potential for nitrification and the diversity of the AAOB in two marine sponges Ircinia strobilina and Mycale laxissima. All of the AmoA sequences obtained from the two sponges clustered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
150
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(161 citation statements)
references
References 51 publications
9
150
1
1
Order By: Relevance
“…This is consistent with data from sponge-derived 16S rRNA gene libraries where both of these phyla are often represented by many different phylotypes (Hentschel et al, 2002;Taylor et al, 2007;Lee et al, 2009). The third most diverse group in this study is the Poribacteria, a candidate phylum that was so far barely detected outside of sponges (but see Mohamed et al, 2010;Pham et al, 2008). Poribacteria are known to be abundant in and widespread among sponges (Fieseler et al, 2004;Lafi et al, 2009).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with data from sponge-derived 16S rRNA gene libraries where both of these phyla are often represented by many different phylotypes (Hentschel et al, 2002;Taylor et al, 2007;Lee et al, 2009). The third most diverse group in this study is the Poribacteria, a candidate phylum that was so far barely detected outside of sponges (but see Mohamed et al, 2010;Pham et al, 2008). Poribacteria are known to be abundant in and widespread among sponges (Fieseler et al, 2004;Lafi et al, 2009).…”
Section: Resultssupporting
confidence: 91%
“…Generally, the species-specific bacterial community consists of Plus-and MinusOTUs, however, the proportions of both OTU types within single phyla differ (Figure 7). Poribacteria are represented by only Plus-OTUs, which is in agreement with the fact that they were so far almost exclusively found within sponges (but see Mohamed et al, 2010;Pham et al, 2008). Chloroflexi, Acidobacteria and Gemmatimonadetes contain many more Plus-than Minus-OTUs whereas the opposite is true for e.g.…”
Section: Resultssupporting
confidence: 82%
“…Although our understanding of the microbial diversity in sponges is rapidly improving, much remains unknown about the activity of these microbes (Taylor et al, 2007a). Specific microbially mediated processes within sponges, such as photosynthesis, sulphate reduction, nitrogen fixation and nitrification, have been quantified and in many cases the relevant microbes have been identified (Wilkinson and Fay, 1979;Wilkinson, 1983;Diaz and Ward, 1997;Wilkinson et al, 1999;Hoffmann et al, 2005Hoffmann et al, , 2009Hallam et al, 2006;Bayer et al, 2008;Mohamed et al, 2008aMohamed et al, , 2009Steger et al, 2008). These studies, which have utilized methods such as isotope enrichments, metagenomics and functional gene analyses, have extended our knowledge of symbiont function in sponges, yet they remain focused on specific processes or particular functional groups of organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular techniques have revealed that these bacterial communities are remarkably diverse and include many novel bacteria (Taylor et al, 2007;Mohamed et al, 2008c;Webster and Blackall, 2009). Symbiotic relationships between sponges and microorganisms are considered to contribute to the health and nutrition of sponges (Mohamed et al, 2010). Many studies have shown the metabolic phenotypes of sponge-associated microbes (Taylor et al, 2007;Mohamed et al, 2008dMohamed et al, , 2010, although little evidence exists confirming the contribution of symbiotic microbes to sponge well-being or survival (Webster and Blackall, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Symbiotic relationships between sponges and microorganisms are considered to contribute to the health and nutrition of sponges (Mohamed et al, 2010). Many studies have shown the metabolic phenotypes of sponge-associated microbes (Taylor et al, 2007;Mohamed et al, 2008dMohamed et al, , 2010, although little evidence exists confirming the contribution of symbiotic microbes to sponge well-being or survival (Webster and Blackall, 2009). Exceptions are the translocation of photosynthate from cyanobacteria to the host sponge (Wilkinson, 1979) and a decrease in health status of sponges associated with loss of cyanobacteria (Thacker, 2005).…”
Section: Introductionmentioning
confidence: 99%